Blockchain in Around the World - Sadiku, Matthew N. O; Chukwu, Uwakwe C.; Sadiku, Janet O. (International Journal on Human-Computing Studies, 2023)
In recent years, global interest in blockchain technologies and their possible impact have permeated the public consciousness. Blockchain is essentially software made up of records of digital transactions that are grouped together into “blocks” of information and shared securely across computers on a shared network. Blockchain pilot programs are being implemented around the world in a variety of ways. Numerous nations are presently preferring the utilization of blockchain technology. The rapid growth of blockchain has prompted governments around the world to explore ways to regulate it. This paper summarizes the current blockchain adoption and regulation in ten countries.